Psychotherapy in psychiatry: the current situation and future directions in Germany - Schnell, Knut; Herpertz, Sabine (European archives of psychiatry and clinical neuroscience, 2011)
The aim of this article is to review how psychotherapy is dispensed to patients in psychiatric treatment and to render the future perspectives of psychotherapy in psychiatric outpatient and inpatient care in Germany. We demonstrate that—according to the currently available data about healthcare providers, allocation of financial resources and curricular regulations—the presently used definition of the term “psychotherapy” is ambiguous. One major problem for the application of psychotherapy in psychiatry is obviously constituted by the dominance of the major guideline therapies (“Richtlinienverfahren”) within psychiatric services. Here, guideline therapies do not meet the needs of a significant proportion of acutely, severely and/or chronically ill psychiatric patients and restrain the application of scientifically approved, disorder-oriented and context compliant interventions in psychiatric practice. As a future perspective, we suggest that the training of psychiatrists should impart profound interpersonal skills and provide the competence to offer psychotherapy within a multimodal, modular, and flexible treatment plan on the background of the self-conception of psychiatry as a medical discipline. Moreover, future concepts of psychiatric psychotherapy should promote an evidence-based selection and application of scientifically approved, disorder-oriented, and integrative treatment methods, which are available in growing number.
Gesehen am 25.10.2022